Predictors of mortality among adolescents and young adults living with HIV on antiretroviral therapy in Dar es Salaam, Tanzania: a retrospective cohort study. Issue 2 (22nd February 2022) - Amour, Maryam A.; Shayo, Grace A.; Matee, Mecky M.; Machumi, Lameck; Rugarabamu, Angelica; Aris, Eric A.; Sunguya, Bruno F.; Mugusi, Ferdinand M.
Abstract: Introduction: Global AIDS‐related deaths have declined by only 10% among adolescents since its peak in 2003. This is disproportionately low compared to a decline of 74% among children aged 0–9 years old. We determined the magnitude of, and predictors of mortality among adolescents and young adults living with HIV on antiretroviral therapy (ART) in Dar‐es‐Salaam, Tanzania. Methods: A retrospective cohort study was conducted among adolescents (aged 10–19) and young adults (aged 20–24) living with HIV and enrolled in care and treatment centres in Dar es Salaam, Tanzania between January 2015 and December 2019. Data were analysed using STATA version 16. Cumulative hazard curves were used to estimate and illustrate 1‐year mortality. Predictors for mortality were assessed by the Fine and Gray competing risk regression model. Sub‐hazard ratios (SHR) and 95% confidence intervals (95% CI) were then reported. Results: A total of 15, 874 young people living with HIV were included: 4916 (31.3%) were adolescents and 10, 913 (68.7%) were young adults. A total of 3843 (77.5%) adolescents and 9517 (87.2%) young adults were female. Deaths occurred in 2.3% (114/4961) of adolescents and 1.2% (135/10, 913) of young adults ( p < 0.001). Over a follow‐up of 9292 person‐years, the mortality rate was 3.8 per 100 person years [95% CI 3.2–4.6/100 person‐years] among adolescents and 2.1 per 100 person‐years among young adults [95% CI 1.8–2.5/100 person‐years]. Independent predictors of mortality among adolescents were male sex (adjusted (SHR) aSHR = 1.90, 95% CI: 1.3–2.8), CD4 count < 200 cells/mm 3 (aSHR = 2.7, 95% CI: 1.4–5.0) and attending a private health facility (aSHR = 1.7, 95% CI: 1.1–2.5). Predictors of mortality among young adults were CD4 count < 200 cells/mm 3 (aSHR = 2.8, 95% CI 1.7–4.5), being underweight (aSHR = 2.1, 95% CI: 1.4–3.3) and using nevirapine‐based therapy (aHR = 8.3, 95% CI: 3.5–19.5). Conclusions: The mortality rate for persons living with HIV and on ART in Tanzania was significantly higher in adolescents than young adults. Age‐ and sex‐specific risk factors identify targets for intervention to reduce mortality among affected adolescents and young adults.